Multiplex PCR (polymerase chain reaction) assay for detection of E. coli O157:H7, Salmonella sp., Vibrio cholerae and Vibrio parahaemolyticus in spiked shrimps (Penaeus monodon) - Fakruddin, M.D.; Sultana, Mahmuda; Ahmed, Monzur Morshed; Chowdhury, Abhijit; Choudhury, Naiyyum (© 2013 Pakistan Journal of Biological Sciences, 2016)
This article was published in the Pakistan Journal of Biological Sciences [© 2013 Asian Network for Scientific Information] and the definite version is available at : http://dx.doi.org/10.3923/pjbs.2013.267.274. The Journal's website is at: http://scialert.net/abstract/index.php?doi=pjbs.2013.267.274